Against the (Campaign) Grain: The Cross-Cutting Effects of Authoritarianism in Political Campaigns. Issue 2 (3rd April 2021) - Chen, Philip Gordon; Housholder, Elizabeth
Abstract : For decades politicians focused their campaigns on issues that primed feelings of normative or existential threat among voters. Whether national security, increasing crime rates, or civil unrest, these campaign appeals led voters to consider external political threats. We examined one particular issue, national security, and showed that Republican candidates in particular benefitted from campaigning on this issue. When the campaign context featured national security issues, Republican candidates benefitted as highly authoritarian Democrats increased their support of Republican candidates. Interestingly, similar appeals did not benefit Democratic candidates. We found that the political context raised perceptions of threat and increased the influence of authoritarianism among voters, but these perceptions were asymmetrical across partizan and psychological divides. This asymmetry led to drastically different candidate evaluations and political behavior.